Interpolating silicon photomultipliers - Fischer, Peter; Piemonte, Claudio (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2013)
We present the novel Interpolating Silicon PhotoMultiplier (ISiPM) concept which provides the spatial position of photon clusters with high resolution. Individual APD cells of the ISiPM area are not connected to a common readout electrode, but each cell is connected to one of several output channels. The most straight forward embodiment is a rectangular device with four outputs located (conceptually) in the corners. The assignment of each cell to one of the channels is chosen such that the center of gravity of an arbitrarily shaped group of cells can be reconstructed as (for instance) the weighted sum of the corner signals. Due to the finite size of the cells, this exact goal can only be approximated and residual systematical errors remain. A first prototype device with 100×100 cells on an area of 7.3×7.45mm2 has been fabricated at FBK and operated successfully. Individual LYSO crystals of ≈2mm width in a block array can be identified easily. The ISiPM concept offers good spatial resolution on large areas with a moderate number of readout channels so that it is a promising device for instance for PET detectors.